2021
DOI: 10.1186/s12889-021-12175-9
|View full text |Cite
|
Sign up to set email alerts
|

Global trends and predictors of face mask usage during the COVID-19 pandemic

Abstract: Background Guidelines and recommendations from public health authorities related to face masks have been essential in containing the COVID-19 pandemic. We assessed the prevalence and correlates of mask usage during the pandemic. Methods We examined a total of 13,723,810 responses to a daily cross-sectional online survey in 38 countries of people who completed from April 23, 2020 to October 31, 2020 and reported having been in public at least once d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
61
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 22 publications
11
61
3
Order By: Relevance
“…However, this age group was and continues to be criticized for not following the non-pharmaceutical rules to limit the spread of SARS-CoV-2 (45). While several national publications supported the results of the present study (46,47), some studies found no association between compliance of wearing masks and age groups (44,48), and others detected a positive association between increasing age and the likelihood of wearing a mask in public areas (39,49). The mixed results suggest that the strength of the association varies according to the age group assignment and sample size per age group, which should be considered for the study at hand.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, this age group was and continues to be criticized for not following the non-pharmaceutical rules to limit the spread of SARS-CoV-2 (45). While several national publications supported the results of the present study (46,47), some studies found no association between compliance of wearing masks and age groups (44,48), and others detected a positive association between increasing age and the likelihood of wearing a mask in public areas (39,49). The mixed results suggest that the strength of the association varies according to the age group assignment and sample size per age group, which should be considered for the study at hand.…”
Section: Discussionsupporting
confidence: 77%
“…The mixed results suggest that the strength of the association varies according to the age group assignment and sample size per age group, which should be considered for the study at hand. In general, some studies indicated the compliance of German citizens toward this measure to be high (49). However, when compared to other European and predominantly Asian countries, the compliance of the German population was relatively low during the second wave (20,50).…”
Section: Discussionmentioning
confidence: 99%
“…Females reported lower levels of risk for poor compliance compared to males, but this difference was not statistically significant. Although lack of gender difference in PHBs has been reported in India [ 31 ], the finding of few gender differences in compliance is not fully consistent with past research [ 29 , 36 40 ]. However, it is important to note that the meta-analysis conducted by Moran and Del Valle [ 39 ] was based on studies that used variable-centered approaches with an emphasis on mean gender differences.…”
Section: Discussionmentioning
confidence: 62%
“…Latent class membership can also be used to predict an observed distal outcome, which, in the current study, is compliance with public health recommendations during the early phase of the pandemic. Moreover, given increasing empirical evidence that women are more likely than men to engage in PHBs during epidemics and pandemics [ 29 , 36 39 ] as well as in health behaviors more generally [ 40 ], we examined possible gender differences in the relations between typologies of stress appraisal and problem-focused coping and PHBs.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the COVID-19 pandemic, the European Environment Agency [ 1 ] reported in June 2021 a waste of 170,000 tons of face masks and estimated an additional global warming potential of 2.4–5.7 million tons of equivalent carbon dioxide (CO ). Although the use of protective masks is significantly associated with sociodemographic factors, social behaviors and prevention policies, it has been established in most of the global population [ 2 , 3 ]. The massive use of protective masks will be linked to the epidemiological progress of the pandemic.…”
Section: Introductionmentioning
confidence: 99%